2023
DOI: 10.3892/etm.2023.11934
|View full text |Cite
|
Sign up to set email alerts
|

Active constituents of saffron (Crocus sativus L.) and their prospects in treating neurodegenerative diseases (Review)

Abstract: Crocus sativus L. (saffron) is widely used as a traditional spice for flavoring, coloring and medicinal purposes. As a traditional Chinese herb, saffron promotes blood circulation, removes blood stasis, cools and detoxifies the blood, relieves depression and calms the mind. According to modern pharmacological studies, the active constituents of saffron, including crocetin, safranal and crocus aldehyde, exhibit antioxidant, anti-inflammatory, mitochondrial function-improving and antidepressant effects. Thus, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…Studies have demonstrated that elevated levels of pro-inflammatory factors such as interleukins are found in the cerebrospinal fluid of patients suffering from depression. This leads to thinks that there might be a connection between the inflammatory process and the depression itself (Yang et al, 2023). In depressed patients, we observe a higher plasma level of corticosterone compared to normal individuals.…”
Section: Improvement Of Cognitionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies have demonstrated that elevated levels of pro-inflammatory factors such as interleukins are found in the cerebrospinal fluid of patients suffering from depression. This leads to thinks that there might be a connection between the inflammatory process and the depression itself (Yang et al, 2023). In depressed patients, we observe a higher plasma level of corticosterone compared to normal individuals.…”
Section: Improvement Of Cognitionmentioning
confidence: 53%
“…According to the studies, crocin may increase the expression of BDNF and tropomyosin receptor kinase B (TrkB) which also plays an important role in synaptic plasticity. Additionally, crocin may increase also the expression of memory related protein postsynaptic À95 which has a key role in bidirectional synaptic plasticity and improves learning and memory ability in rats (Lin et al, 2019;Yang et al, 2023).…”
Section: Improvement Of Cognitionmentioning
confidence: 99%
“…Saffron is a potential therapeutic agent that can modulate this pathological signaling process in Alzheimer's disease. Saffron is shown to potentially inhibit the formation of Aβ plaques, suggesting it might interfere with the cleavage of APP or the aggregation of Aβ peptides [ 40 ]. Moreover, saffron is linked to the normalization of impaired glutamate recycling, indicating its possible role in protecting synaptic function [ 40 ] ( Fig.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…A few diferent experimental models and approaches have been proposed, but in the last years, research focused mostly on Alzheimer's disease and Parkinson's disease. Several authors have recently published reviews on the topic focusing on the safron or its constituents [17,18]. Recent paper reported potential mechanisms related to the possible efects of safron or safron constituents on some CNS diseases and the most relevant ones are summarized in Table 1.…”
Section: Bioactivity Of Safron Related To Cns Diseasesmentioning
confidence: 99%